Synthesis and characterization of EVA-montmorillonite cloisite clay nanocomposites - Abdel Hafiz, Ali Ahmed (AUC Knowledge Fountain, 2012)
Polymer Layered Silicates (PLS) are currently attracting researchers to seek a solution to the challenge of delaminating the clay layers. In this study, investigation of the morphology of 5 wt% of different organically-modified (15A, 20A and 30B) and non-modified (Na+) Cloisite Montmorillonite clays blended with Polyethylene co Vinyl Acetate (EVA) was conducted. Synthesis of the composites was made by one or more of the following techniques: solution compounding, sonication, and extrusion to overcome stacking of the clay layers. Composites were characterized by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) to reveal information about their morphologies. Composites were subjected to tensile testing to relate changes in mechanical behavior to the clay type and the obtained morphologies. Results show varieties of polymer layered silicate structures from immiscible to intercalated and/or exfoliated structures. Eva-Na+ composites showed the least uniform dispersion and exfoliation, which is attributed to the modifier. Both EVA-15A and EVA-20A composites showed good dispersion and delamination of the clay layers, which was motivated by sonication and enhanced by extrusion. The type of organic modifier appeared to play a more dominant role than the amount of organic modifier, as confirmed by the results of the XRD analysis of EVA-15A and EVA-20A which have the same type of organic modifier. Good dispersion and delamination was also observed for EVA-30B, which is attributed to the nature of the organic modifier, which favors interaction with the acetate group in EVA and contributed to improvements in mechanical properties.